Parcours migratoires et re-constructions identitaires de femmes d'ascendance maghrébine à Montréal - Boukerrou, Yasmine (Université du Québec à Montréal, 2022)
Keywords: Femmes; Maghrébins

Corps-fait-histoire dans le processus de mondialisation, de migration et d'insertion: parcours de femmes immigrantes péruviennes à Montréal - Rojas-Viger, Celia (Université de Montréal, 2004)
Keywords: Femmes; Péruviens

L'emploi des femmes judéo-marocaines à leur arrivée à Montréal (1956-1978) - Néméh-Nombré, Philippe (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Femmes; Juifs; Maghrébins; Marocains; Travail

Le Montreal Council of Women / Conseil des Femmes de Montréal, de 1940 à 1967, à travers les questions de planification urbaine, d'immigration et des femmes dans le monde du travail - Hilairet, Sabine (Université d'Angers, 2003)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Travail

Les Filles du Roy de Pointe-aux-Trembles et de Rivière-des-Prairies - Pomerleau, Gisèle (Centre des femmes de Montréal-Est/Pointe-aux-Trembles, 2017)
Keywords: Femmes; Filles du Roi; Mariage; Pointe-aux-Trembles; Quartiers; Rivière des Prairies

Immigrant Women Entrepreneurs in Montreal: Building Business and Lives - Simpson, Joni (Université Concordia, 2006)
Keywords: Femmes

Qui a le droit d’entrer et de rester au Canada? Quand ces questions s’invitent chez les Franco-Québécoises (1946-1955) - Trimble, Sheena (Études canadiennes / Canadian Studies, 2022)
Keywords: Femmes

Entrepreneurs in the New Economy: Immigration and Sex Effects in the Montreal Metropolitan Area - Paré, Sylvie; Therasme, Kelogue (Journal of International Entrepreneurship, 2010)
The recent literature on women’s entrepreneurship shows that they are underrepresented in the main stream economy when compared to their male counterparts, a phenomenon typically observed in other urban contexts. Approximately 30% of the entrepreneurs in the Montreal metropolitan area are women, active in a variety of sectors of the general economy. Their underrepresentation is still greater in the new economy, that is, those sectors that are knowledge-based and/or specialized in information technologies and communications. In this article, we examine the place of female entrepreneurs in the larger economy and in the new economy as related to their immigrant and/or ethnic origins. We seek in this paper to establish a comparative analysis of the situation of women entrepreneurs in immigrant-origin groups, focusing our attention on both the presence of women in entrepreneurial positions and the differential impact associated with membership in an immigrant-origin group. Based on data derived from Scott's Directory of 2007, we first determined an operational definition of the new economy and then analyzed the data from the perspective of sex and ethnic/immigrant origin. New economy enterprises represent approximately 12% of businesses in the Montreal metropolitan area, the majority of which are of the knowledge-based variety, and there is a relative, statistically significant absence of women from such enterprises. At the same time, there is a significantly greater presence of women drawn from minority groups, that is, from groups other than the Anglo-Canadian and French-Canadian dominant groups.
Number: 2
Keywords: Femmes; Travail

Statut d'immigration, agentivité et référents identitaires: l'expérience migratoire d'immigrantes maghrébines - Morin, Marie-Pier (Université de Montréal, 2009)
Keywords: Femmes; Maghrébins

Your Roots Will Be Here, Away from your Home: Migration of Greek Women to Montreal 1950-1980 - Dounia, Margarita (Université McGill, 2004)
Keywords: Femmes; Grecs

Agents of Change, Colours of Resistance: The Socio-Economic Integration of Filipina Live-In Caregivers in Montreal - Kapiga, Isabelle (Université Concordia, 2009)
Keywords: Femmes; Philippins

L’immigration féminine au Canada durant les années 1920: la mise en place d’une politique fondée sur le "genre" - Vallée, Marie-Hélène (Recherches féministes, 2002)
Number: 2
Keywords: Britanniques; Femmes

La migration féminine qualifiée d’origine sud-américaine à Montréal: ressources culturelles et symboliques, et stratégies d’accès au marché de l’emploi - Guillen Castro, Maritza (Université de Montréal, 2009)
Keywords: Femmes; Travail

Maternidad y migración: Entre recuerdos y pensares: Historias de vida de quince mujeres latinoamericanas que habitan en Montréal (Canadá) - Bedoya Idrobo, Luz Marina (Université de Montréal, 2009)
Keywords: Femmes; Latino-Américains

Le parcours de réorientation professionnelle d’immigrantes hautement qualifiées à Montréal: une étude exploratoire - Germain, Danielle (Université de Montréal, 2013)
Keywords: Famille; Femmes; Travail

Facteurs déterminants des styles parentaux des mères haïtiennes immigrantes à Montréal - Jean-Baptiste, Larissa (Université de Montréal, 2002)
Keywords: Famille; Femmes; Haïtiens

Families, Lovers and their Letters: Italian Postwar Migration to Canada - Cancian, Sonia (University of Manitoba Press, 2010)
Keywords: Famille; Femmes; Italiens

"Filles du roi et Filles de la cassette" : l'immigration féminine au Canada (1663-1673) et en Basse-Louisiane (1710-1730) - Pelletier Lewis, Rose (Université de Sherbrooke, 2017)
Keywords: Femmes; Filles du Roi

Les Filles du Roy: pionnières de Montréal - Société d'histoire des Filles du Roy (Septentrion, 2017)
Keywords: Femmes; Filles du Roi

One (Wo)man’s Shopping is the Same (Wo)man’s history? Immigration, Advertisement and Consumption Patterns in the Greek community of Montreal 1960s-1970s - Pabst, Stavroula (Études canadiennes / Canadian Studies, 2009)
Number: 1
Keywords: Femmes; Grecs; Publicité

"My Love, How Different Life Is Here..." A Young Italian Woman's Impressions of Postwar Montreal - Cancian, Sonia (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Femmes; Italiens; Langue; Travail

Le genre d’une migration post-coloniale: de Meknès (Maroc) à Montréal (Québec) - Cohen, Yolande (Genre et Histoire, 2010)
Number: 6
Keywords: Femmes; Féminisme; Historiens; Juifs; Marocains

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage